ENHANCING APRON MOVEMENT CONTROL JOB PERFORMANCE THROUGH CONTEXTUAL TEACHING AND LEARNING IN AVIATION ENGLISH - Eska Nugraha, Minulya; Putra, Iwansyah; Yuniar, Dwi Candra; Febiyanti, Herlina; Abdullah, Anton; Hermala, Zusnita (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
Low proficiency in technical English, especially radiotelephony communication, remains a major challenge among aviation cadets. This skill is a core requirement for Apron Movement Control (AMC) officers to ensure effective and safe ground operations. This study aims to examine the effect of the Contextual Teaching and Learning (CTL) approach on improving AMC cadets’ Aviation English competence. A quantitative approach with a one–group pretest–posttest design was employed. The participants consisted of 48 cadets from class MBU 03 at the Palembang Aviation Polytechnic. Data were collected through pretest and posttest assessments and analyzed using the Shapiro–Wilk normality test and the Paired Sample T-test. The findings revealed a significant improvement in cadets’ competence, as indicated by an increase in the mean score from 215.52 (pretest) to 435.83 (posttest). The correlation test (r = 0.721; sig = 0.000) and the t-test (sig = 0.000 < 0.05) confirmed a statistically significant effect of CTL implementation. The results demonstrate that the CTL approach effectively enhances Aviation English competence by linking instructional materials with authentic operational contexts. This study introduces an innovative integration of CTL in Aviation English learning for AMC operations, offering a contextualized and industry-relevant model for vocational aviation education.